2020
DOI: 10.1002/smr.2316
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the criticality of user‐reported issues through their relations with app rating

Abstract: App quality impacts user experience and satisfaction. As a consequence, both app ratings and user feedback reported in app reviews are directly influenced by the user-perceived app quality. Through an empirical study involving 210,517 reviews related to 317 Android apps, in this paper, we experiment with the combined usage of app rating and user reviews analysis (i) to investigate the most important factors influencing the perceived app quality, (ii) focusing on the topics discussed in user review that most re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Statistical analysis is used in many papers to report research results (Martin et al 2015;Sänger et al 2016;Di Sorbo et al 2020), demonstrate their significance (Vasa et al 2012;Khalid et al 2016), and draw conclusions of a large population of reviews by analysing their tiny portion (Pagano and Maalej 2013;Mercado et al 2016;Wang et al 2020a). We observed an interest in use of descriptive and inferential techniques for Content Analysis e.g., Vasa et al (2012), Pagano and Maalej (2013), Mercado et al (2016), Guzman et al (2018), and Wang et al (2020a).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Statistical analysis is used in many papers to report research results (Martin et al 2015;Sänger et al 2016;Di Sorbo et al 2020), demonstrate their significance (Vasa et al 2012;Khalid et al 2016), and draw conclusions of a large population of reviews by analysing their tiny portion (Pagano and Maalej 2013;Mercado et al 2016;Wang et al 2020a). We observed an interest in use of descriptive and inferential techniques for Content Analysis e.g., Vasa et al (2012), Pagano and Maalej (2013), Mercado et al (2016), Guzman et al (2018), and Wang et al (2020a).…”
Section: Discussionmentioning
confidence: 84%
“…Classification is by far the most common type of app review analysis found in the literature: 58% of publications describe techniques for classifying reviews. Classification can be used to separate informative reviews from those that are uninformative (e.g., Oh et al 2013;Chen et al 2014;Di Sorbo et al 2016;Di Sorbo et al 2020), spam (Chandy and Gu 2012) or fake (Martens and Maalej 2019b). Informative reviews can be subsequently classified to detect user intentions (e.g., Zhou et al 2020) and discussion topics (e.g., Di van Vliet et al 2020).…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Software maintenance involves tasks for mitigating potential defects in the code, as well as for evolving it according to the users' emerging needs [1]. Thus, it is crucial for the success of software projects.…”
Section: Introductionmentioning
confidence: 99%
“…Software developers intensively rely on of software repositories [1], [9], [29] and written communication channels [7], [24] for exchanging relevant information about the ongoing development tasks and the status of overall project progress. Development teams contributing to the software repositories [1], [9], [29] are globally distributed [7]: they often (i) communicate in unstructured form through mailing lists [5] and chats [2], (ii) discuss problems and related solutions over issue trackers [20], [21] and Question & Answer forums (e.g., Stack Overflow) [31], and (iii) acquire feedback posted by users on dedicated channels, as in the case of mobile apps (e.g., app stores) [14]. Therefore, valuable information is disseminated (and scattered) over semi-structured and unstructured software artifacts [7], [9], [24].…”
Section: Introductionmentioning
confidence: 99%